1996
DOI: 10.1021/ja953525d
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Electronic and Geometric Structure of Colloidal Ti0·0.5THF

Abstract: The reduction of TiBr4·2THF using K[BEt3H] yields the hydrogen-free organosol Ti·0.5THF. According to the HRTEM (high-resolution transmission electron microscopy), EDX (energy-dispersive X-ray) fluorescence, XPS (X-ray photoelectron spectroscopy), XANES (X-ray absorption near edge structure), and EXAFS (extended X-ray absorption fine structure) data, this nanoparticulate metal colloid consists of very small Ti particles in the zerovalent state, stabilized by intact THF molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
63
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 41 publications
5
63
1
Order By: Relevance
“…However, the constant intensity ratio A/B after different sputtering cycles allow the hypothesis that peak B results from the outermost Mn atoms of the colloid particles, interacting with oxygen from the coordinated THF molecule, while peak A represents the innermost atoms. This peak assignment agrees with our structural model of the metal colloid particles [1,2] and confirms that the sample under study consists mainly of intact, non-oxidized metal colloid particles and a partly oxidized sample area. Note that we have observed that only the outermost spherical region of the sample was brown coloredÐ an indication of MnO 2 Ðwhile the inner region was black.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…However, the constant intensity ratio A/B after different sputtering cycles allow the hypothesis that peak B results from the outermost Mn atoms of the colloid particles, interacting with oxygen from the coordinated THF molecule, while peak A represents the innermost atoms. This peak assignment agrees with our structural model of the metal colloid particles [1,2] and confirms that the sample under study consists mainly of intact, non-oxidized metal colloid particles and a partly oxidized sample area. Note that we have observed that only the outermost spherical region of the sample was brown coloredÐ an indication of MnO 2 Ðwhile the inner region was black.…”
supporting
confidence: 88%
“…[2] Here we discuss the synthesis of the hydrogen-free organosol [Mn × 0.3THF] x together with a detailed characterization of the product by a combination of physical methods. The use of MnBr 2 × 2THF as the starting material for the salt reduction and a subsequent cooling step to ±78 C allows more than 95 % of the insoluble byproduct KBr to be removed from the manganese sol.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray absorption spectroscopy (XAS) has been proven to be a spectroscopic technique especially well suited for the investigation of the electronic and geometric structure of small metallic particles in the absence of welldefined crystal structures. 4,5 While this holds especially for the detailed analysis of the extended x-ray absorption fine structure (EXAFS) and its rich information content on structure parameters such as bonding lengths and coordination numbers, 6 the additional information exposed by the X-ray absorption near-edge structure (XANES) has often been disregarded.…”
Section: Introductionmentioning
confidence: 99%